2008
DOI: 10.1002/ajmg.b.30732
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in fragile X‐associated tremor/ataxia syndrome (FXTAS): Comparison with Alzheimer's disease

Abstract: Background-Neurocognitive deficits in fragile X-associated tremor/ataxia syndrome (FXTAS) involve attentional control, working memory, executive functioning, and declarative and procedural learning. To date, no studies comparing FXTAS with other dementias have been done. We characterize the dementia in FXTAS, comparing it with Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(134 citation statements)
references
References 39 publications
5
123
2
2
Order By: Relevance
“…Dementia was found in 21-50% males with FXTAS (32,36). In females with FXTAS, however, dementia is far less common (36,37) and it has been reported in only a few cases (41)(42)(43)(44)(45). Females with FXTAS may also exhibit parkinsonism, although at a lower rate than in males with FXTAS (34).…”
Section: Fxtasmentioning
confidence: 98%
See 2 more Smart Citations
“…Dementia was found in 21-50% males with FXTAS (32,36). In females with FXTAS, however, dementia is far less common (36,37) and it has been reported in only a few cases (41)(42)(43)(44)(45). Females with FXTAS may also exhibit parkinsonism, although at a lower rate than in males with FXTAS (34).…”
Section: Fxtasmentioning
confidence: 98%
“…After the tremor onset, the median onset of ataxia was 2 years later; onset of falls was 6 years later; dependence on a walking aid was 15 years later; and death was 21 years later (35). The rate of progression of FXTAS varies and life expectancy is between 5 to 25 years after the onset of the symptoms (36).…”
Section: Fxtasmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive decline in FXTAS usually occurs in men, after a long duration of extrapyramidal disturbances, but it may also occur in women. Typically in men, a clinical picture similar distinct from Alzheimer´s disease (Seritan et al, 2008), and more similar to patients with fronto-temporal lobar degeneration occurs (FTLD) (Burgeois et al, 2009). Although there is little evidence from MRI in these patients, particularly in women (Al Hinti et al, 2007;Karmon et al, 2008), more recently, two cases of mother-to-daughter transmission were reported (Rodriguez-Revenga et al, 2010).…”
Section: Advances In Neuroimaging In Fxtas and Future Needsmentioning
confidence: 99%
“…In males, initially mild cognitive problems can accomplish criteria for dementia after 5 to 10 years of evolution (Grisby et al, 2007). Extension of the neurodegenerative process to prefrontal and temporal structures seems to account for the progression of cognitive defects in FXTAS patients (Seritan et al, 2008). While balance problems and tremor seem to be the consequence of the progressive degeneration of middle cerebellar peduncles and associated cerebellar structures, both cognitive and behavioural problems in FXTAS are associated with diffuse cortical and white-matter subcortical degeneration (Hashimoto et al, 2011).…”
Section: Clinical and Cognitive Overviewmentioning
confidence: 99%